2022
DOI: 10.1101/2022.07.18.22277740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of COVID-19 vaccine on long-COVID: A 2-year follow-up observational study from hospitals in north India

Abstract: Introduction: Long-COVID syndrome encompasses a constellation of fluctuating, overlapping systemic symptoms after COVID. We know that vaccination reduces the risk of hospitalization and death but not of re-infections. How these vaccines impact long-COVID is under debate. The current study was designed to analyze the patterns of long-COVID amongst vaccinated and unvaccinated hospitalized patients during the three waves in India. Methods: The computerized medical records of the patients admitted to a group of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The main information and the data for the meta-analysis of the included studies are shown in Table 1 and Table S2 of the Supplementary Material, respectively. Among them, 15 articles were accepted or published [15,16,[21][22][23][24][25][26][27][28][29][30][31][32][33]] and 3 articles were preprints [7,34,35]. All of the studies were observational, including 12 cohort studies, 1 case-control study, and 5 cross-sectional studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The main information and the data for the meta-analysis of the included studies are shown in Table 1 and Table S2 of the Supplementary Material, respectively. Among them, 15 articles were accepted or published [15,16,[21][22][23][24][25][26][27][28][29][30][31][32][33]] and 3 articles were preprints [7,34,35]. All of the studies were observational, including 12 cohort studies, 1 case-control study, and 5 cross-sectional studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…This nding is in line with previous studies showed that the risk of post-COVID complaints are differed as function of vaccinate status. In that, post-COVID complaints are more common in non-vaccinated individuals compared to vaccinated individuals 45,47,48,49,50,51,52,53 . In the current study, been hospitalized didn't contribute to the explained variances in post-COVID impairments.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies suggest a significant protective effect [18][19][20][21][22][23][24][25][26][27] , e.g., a reduced risk of the diagnosis of PASC or experiencing certain PASC symptoms. Meanwhile, other studies indicate mixed effects revealing considerable variations across different age groups, various dominant virus strains, and distinct PASC symptoms [28][29][30][31][32] , or even suggesting counter-protective effects 33,34 . Moreover, the majority of existing studies have reported effects by comparing breakthrough infection to infections in unvaccinated individuals, which is conditional on the infection status 18,21,24,26,28,29,35 .…”
Section: Introductionmentioning
confidence: 99%